Activation loop phosphorylation regulates B‐Raf in vivo and transformation by B‐Raf mutants. (10th December 2015) - Köhler, Martin; Röring, Michael; Schorch, Björn; Heilmann, Katharina; Stickel, Natalie; Fiala, Gina J; Schmitt, Lisa C; Braun, Sandra; Ehrenfeld, Sophia; Uhl, Franziska M; Kaltenbacher, Thorsten; Weinberg, Florian; et al.
Abstract: Despite being mutated in cancer and RASopathies, the role of the activation segment (AS) has not been addressed for B‐Raf signaling in vivo . Here, we generated a conditional knock‐in mouse allowing the expression of the B‐Raf AVKA mutant in which the AS phosphoacceptor sites T599 and S602 are replaced by alanine residues. Surprisingly, despite producing a kinase‐impaired protein, the Braf AVKA allele does not phenocopy the lethality of Braf ‐knockout or paradoxically acting knock‐in alleles. However, Braf AVKA mice display abnormalities in the hematopoietic system, a distinct facial morphology, reduced ERK pathway activity in the brain, and an abnormal gait. This phenotype suggests that maximum B‐Raf activity is required for the proper development, function, and maintenance of certain cell populations. By establishing conditional murine embryonic fibroblast cultures, we further show that MEK/ERK phosphorylation and the immediate early gene response toward growth factors are impaired in the presence of B‐Raf AVKA . Importantly, alanine substitution of T599/S602 impairs the transformation potential of oncogenic non‐V600E B‐Raf mutants and a fusion protein, suggesting that blocking their phosphorylation could represent an alternative strategy to ATP‐competitive inhibitors. Synopsis: B‐Raf activation loop phosphorylation is required for ERK/MAPK signalling and transformation by oncogenic BRAF, but it is dispensable for murine development. Blocking phosphorylation could represent an alternative strategy for treating tumours with BRAF fusion oncogenes. Activation loop phosphorylation sites T599 and S602 are required for maximum B‐Raf activity and MEK/ERK signaling in vivo . Phospho‐site mutant (B‐Raf AVKA ) animals are viable. Unlike truly kinase‐dead B‐Raf mutants, B‐Raf AVKA does not provoke paradoxical ERK pathway activation. Phospho‐site mutants abrogate the transformation potential of non‐V600E B‐Raf mutants incl. the astrocytoma associated FAM131B‐B‐Raf fusion protein. Abstract : B‐Raf activation loop phosphorylation is required for ERK/MAPK signalling and transformation by oncogenic BRAF, but it is dispensable for murine development. Blocking phosphorylation could represent an alternative strategy for treating tumours with BRAF fusion oncogenes.